William Robert Hobson (1831-1880) - Barr, William (ARCTIC, 1986)
In April 1854 Dr. John Rae heard from Inuit at Pelly Bay an account of the last fateful days of Franklin's expedition, missing somewhere to the west for a number of years. . When his report of his discovery reached England, Lady Jane Franklin mounted a private expedition . to search for relics of the expedition on the site. Commander of the expedition was Captain Francis Leopold McClintock . McClintock chose Lieutenant William Robert Hobson as his second-in-command. . William joined the Navy in 1845 and was promoted to mate in 1852, in the interim serving aboard a number of ships on fairly routine duties. Early in 1853 he was appointed mate aboard Rattlesnake, which had been ordered to take supplies to Plover, waiting at Point Barrow, Alaska, in support of McClure's Investigator and Collinson's Enterprise. These latter ships had entered the Arctic via Bering Strait in 1850 to search for the Franklin expedition from the west. . In February, Hobson, with two seamen and nine dogs, set off on a sledge journey northward across the Seward Peninsula to Chamisso Island. This had been set as the rendezvous for Frederick Beechey in Blossom and John Franklin during the latter's second land expedition in 1825-1827, and hence it was thought that Franklin might have headed here again. Hobson's task was to check for signs of Franklin at Chamisso Island. He returned to Rattlesnake on 27 March, having reached his goal and finding no sign of Franklin. . On the basis of this arctic experience, McClintock chose Hobson as his second-in-command for his search expedition aboard Fox. Sailing from Aberdeen on 2 July 1857, Fox made her way north to Melville Bay, where she was caught in the pack ice and drifted for eight months before she could break free. The Fox found more secure winter quarters the next year at Port Kennedy, near the east end of Bellot Strait, and Hobson led several depot-laying trips to the west side of Boothia Peninsula. During a reconnaissance trip in February 1859, McClintock encountered Inuit near Cape Victoria ...